2021
DOI: 10.5114/biolsport.2020.97069
|View full text |Cite
|
Sign up to set email alerts
|

Tart cherry and pomegranate supplementations enhance recovery from exercise-induced muscle damage: a systematic review

Abstract: Phenolic compounds have antioxidant and anti-inflammatory properties and may prevent inflammation and oxidative stress as well as help the athletes to recover from exercise-induced muscle damage (EIMD). Tart cherry (TC) and pomegranate (PG) are two fruits with high content of polyphenols. Their antioxidant and anti-inflammatory properties have recently attracted substantial interest for their potential to reduce strength loss and promote recovery from EIMD. The aims of this review are (1) to summarise the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…For example, IL-6 is a major regulator of myogenesis, and acute IL-6 expression can increase protein synthesis, satellite cell proliferation and can lead to an anti-inflammatory signalling cascade [ 47 ]. In similar previous studies, tart cherry [ 10 , 29 ] and omega-3 polyunsaturated fatty acids [ 8 ] were shown to have an overall treatment effect on attenuating IL-6 compared to placebo, whereas lemon verbena [ 9 ] and pomegranate did not produce treatment effects [ 45 ]. Interestingly, in the present study, IL-6 expression was transiently increased at 0 h post-EIMD in the NPN_1 group, which may aid in the improved strength recovery observed.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, IL-6 is a major regulator of myogenesis, and acute IL-6 expression can increase protein synthesis, satellite cell proliferation and can lead to an anti-inflammatory signalling cascade [ 47 ]. In similar previous studies, tart cherry [ 10 , 29 ] and omega-3 polyunsaturated fatty acids [ 8 ] were shown to have an overall treatment effect on attenuating IL-6 compared to placebo, whereas lemon verbena [ 9 ] and pomegranate did not produce treatment effects [ 45 ]. Interestingly, in the present study, IL-6 expression was transiently increased at 0 h post-EIMD in the NPN_1 group, which may aid in the improved strength recovery observed.…”
Section: Discussionmentioning
confidence: 83%
“…Myostatin was significantly suppressed in the NPN_1 group compared to placebo over the course of the trial, as was the release of fibroblast growth factor 21 (FGF21) in the NPN_1 group at 0 and 2 h. These combined data indicate clinical evidence of attenuation of muscle breakdown with NPN_1 supplementation [ 43 , 44 ], albeit further work is required to identify the minimal clinically important difference in muscle strength recovery and NPN_1 supplementation in a powered trial. In this respect, it is difficult to compare the effect of NPN_1 supplementation on myostatin to other nutritional interventions such as tart cherry, pomegranate and lemon verbena, as many studies into effects on EIMD focus on inflammatory and oxidative stress biomarkers rather than muscle health biomarkers [ 9 , 45 , 46 ]. It is known that acute transient inflammation promotes healing of healthy skeletal muscle [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous nutrients and functional foods have been investigated to help reduce EIMD and accelerate recovery. A recent systematic review demonstrated that tart cherry or pomegranate supplementation are effective nutritional strategies to promote recovery after EIMD including oxidative stress, inflammation, and muscle function (45). Supplementation with cocoa flavonols has also been shown to reduce exercise-induced oxidative stress (11).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence to suggest that functional food-based supplements rich in polyphenols can reduce exercise-induced oxidative stress and inflammation and result in accelerated exercise recovery (7,11,45). The promotion of foods with potential anti-inflammatory properties (cocoa, cherries, pomegranate, blueberries, tea, coffee, grapes, and nuts) is widespread on the internet and social media outlets, and these functional foods and supplements are growing in popularity among athletes and fitness enthusiasts (46,49).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that these studies were conducted only under normoxia [ 1 , 4 , 5 , 6 ]. Another distinctive advantage of TC supplementation has been proposed to reduce subset of oxidative stress markers [ 7 , 8 ]. However, whether this property would improve exercise performance seems to be uncertain.…”
Section: Introductionmentioning
confidence: 99%